Sahel : the populations geopolitics - (:unkn) unknown (My University, 2009)
Geopolitics of Sahelian Africa: Sahel devoted to the study explains the particular sub-population of the area and gave her internal geopolitical, ethnic diversities and the central government, religious differentiations and their use geopolitical kaleidoscope linguistics, population dynamics natural geopolitical dimension of the migration system, high population growth, the relationship between malnutrition and geopolitics.
Keywords: African Research